STUDI PENERAPAN METODE POHON CONTOH (TREE SAMPLING) DALAM PENDUGAAN POTENSI TEGAKAN HUTAN TANAMAN EKALIPTUS - S, Arland; Sadjati, Emy; Ikhwan, Muhammad (Wahana Forestra: Jurnal Kehutanan, 2018)
Management and exploitation of forest products required for planning to be prepared for sustainable forest exploitation and also taking into account aspects of Sustainability. The so-called aspects are production capabilities, ecological functions and social functions. In order to achieve these matters, appropriate data are needed to present information on the potential for existing forest stands through forest inventory activities. In the inventory activity found some problems that occur in terms of cost, time, problems and human resources needed. Factors that will affect the data we get. These inhibiting factors can be overcome by creating three groups using methods that have been developed both in data retrieval techniques and data processing.The sampling method as a suitable and effective method in which the sampling method used in the inventory activity is a conventional method using a plot or a circle plot with the area and sampling determined according to the age class of the stand. In addition, using conventional methods is another method that also has accurate and precise information. Method of sampling trees. This study aims to the effectiveness and effectiveness of tree sampling methods and circular plot methods, making it easier to find an efficient and effective location in the work area of ​​PT. Perawang Sukses Perkasa Petapahan District. The research was conducted in the plantation of industrial plant Ekaliptus (Eucalyptus pellita) located at PT. Perawang Sukses Perkasa Industri Petapahan District, Kampar District, Riau Province. This research was conducted for 2 months ie in May - June 2018. Based on the results of research conducted method of circular plot will be more effective and has a higher level of accuracy than other methods with a value of 2.9% sampling error. When viewed from a relative point of view, the relative average yield using the tree sampling method of 8 trees is more easily done in a circular manner with a relative value of 200.28% and accuracy is still accountable.